Strengthening Coordination Among Extension Service Providers for Improved Provision of Agricultural Extension and Advisory Services: A Case Study from Kenya - Kevan W. Lamm; Fallys Masambuka-Kanchewa; Alexa J. Lamm; Kristin Davis; Silim Nahdy (Journal of International Agricultural and Extension Education, 2020)
Implementation of decentralized and pluralistic policies in provision of extension services has led to increased availability of actors providing extension services to farmers in most developing countries including Kenya. What is unique about extension services providers is that they have a shared goal of improving agricultural productivity. However, in some cases these providers differ in their knowledge regarding the practices or knowledge that is required to improve agricultural productivity. Lack of shared knowledge among providers has contributed to delivery of uncoordinated and duplication of efforts thereby limiting the effectiveness of efforts in extension services delivery. Moreover, in some cases lack of shared knowledge has contributed towards provision of conflicting information which has left farmers confused. Enhancing coordination and collaboration among these representatives is of paramount importance if their efforts to improve agricultural productivity are to be successful. Having structures in place that bring together organizations that have shared goals is an important step in facilitating coordination. This is based on findings of a case study that was conducted in Kenya with the Kenyan Forum for Agricultural Advisory Services (KeFAAS). The results of the study provide insights that can be used as a starting point when strengthening coordination in extension services delivery in decentralized and pluralistic environments.
Keywords: coordination; improved productivity; shared goals; pluralism